PEMBERDAYAAN GURU SMK PENERBANGAN KARTIKA AQASA BHAKTI SEMARANG MELALUI INTEGRASI CHILD FRIENDLY TEACHING MODEL DALAM PROSES PEMBELAJARAN - Nugrahani, Dyah; Musarokah, Siti; Herlambang, Bambang Agus; Sunarya, Sunarya (GANESHA: Jurnal Pengabdian Masyarakat, 2025)
This community service program aims at implementing and integrating CFTM in realizing child-friendly learning. The community service program partner is SMK Penerbangan Kartika Aqasa Bhakti Semarang. The partner is one of the child-friendly schools (SRA) in Semarang City; however, the partner has not implemented child-friendly learning. The priority problems faced by the partner are: 1) There is no common perception between students, teachers, education personnel, principals, and parents regarding the Child-Friendly School concept; 2) There is no joint commitment between students, teachers, education personnel, principals, and parents regarding the Child-Friendly School concept; 3) Students, teachers, education personnel and principals do not yet know the child-friendly learning model; and 4) There has been no implementation of the child-friendly learning model (CFTM) in the partner school. The methods used in this community service program are socialization and training, mentoring learning practices, and monitoring and evaluation. The implementation of this activity shows that the integration of the Child Friendly Teaching Model in learning in vocational schools allows for a transformation in the way teachers teach, especially in building a more positive and participatory learning environment. This is evident from the increase in student interaction, a more conducive classroom atmosphere, and changes in the teacher's approach that prioritizes empathy and active student involvement.